Teachers quality and teacher education at primary education sub-sector in Bangladesh - Mullick, Jahirul Islam; Sheesh, Sameeo (BRAC University, 2010)
The paper discusses the standard of teaching, skills and based on the standards the problems regarding the teachers’ qualification in Bangladesh. It highlights that insufficient knowledge about content pedagogy, not paying adequate attention to intellectual, social, and personal development, ignoring the issues about the diversity of learners, improper and limited use of multiple-instructional strategies, practicing one-way communication, assessing the students’ performance through the conventional methods are the major problems related to teaching skills of primary school teachers in Bangladesh. The article also reveals the shortcomings of the curriculum of Certificate in Education (C-in-Ed), an initial pre-service training for the primary school teachers, e.g., by nature the C-in-Ed curriculum is over-theoretical and it allows the trainee teachers a little time to engage in practice teaching. Besides that, the way forward to producing better qualified teachers have also been discussed in the article.